2022
DOI: 10.1038/s41598-022-09251-4
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering single- and multi-particle trapping dynamics under femtosecond pulsed excitation with simultaneous spatial and temporal resolution

Abstract: Recent theoretical and experimental studies have shed light on how laser trapping dynamics under femtosecond pulsed excitation are fine-tuned by optical and thermal nonlinearities. Here, we present experimental results of trapping of single and multiple polystyrene beads (of 1 μm diameter). We show how integration and synchronization of bright-field video microscopy with confocal detection of backscatter provide both spatial and temporal resolution required to capture intricate details of nonlinear trapping dy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Casimir effect, interactions arising from Zeta potential, etc.) which would require improved three-dimensional video microscopy at a much higher frame-rate; alternatively, only the backscatter signal could be tracked with simultaneous wide-field detection and point detection to achieve the required spatiotemporal resolution that has been demonstrated quite recently 27 .
Figure 4 Backscatter and TPF signal ( a ) when two particles confined within the trap and data collection interval is 400 μs; zoomed plot shows the drag of second particle, ( b ) drag of second particle and data collection interval is 400 ns, and ( c ) residual intensity of backscatter signal fitted with Fourier function (black dotted lines represent the peak-to-peak time) at 18.80 mW average power under pulsed excitation.
…”
mentioning
confidence: 99%
“…Casimir effect, interactions arising from Zeta potential, etc.) which would require improved three-dimensional video microscopy at a much higher frame-rate; alternatively, only the backscatter signal could be tracked with simultaneous wide-field detection and point detection to achieve the required spatiotemporal resolution that has been demonstrated quite recently 27 .
Figure 4 Backscatter and TPF signal ( a ) when two particles confined within the trap and data collection interval is 400 μs; zoomed plot shows the drag of second particle, ( b ) drag of second particle and data collection interval is 400 ns, and ( c ) residual intensity of backscatter signal fitted with Fourier function (black dotted lines represent the peak-to-peak time) at 18.80 mW average power under pulsed excitation.
…”
mentioning
confidence: 99%
“…In addition, depending on the medium's refractive index, in a water-glycerol (70:30) mixture, the position of stable trapping was observed to be shifted [5]. A similar shift was observed for trapping of the second particle (or multiple particles) within a single potential well [6]. The intricate dynamics of single-and multi-particle trapping were resolved by simultaneously detecting the backscatter intensity profile and the two-photon fluorescence signal [7].…”
Section: Introductionmentioning
confidence: 73%
“…To enhance the intensity in the future, it is possible to use pulsed illumination [35]. Simulations have shown that the intensity of the field in the hook and the optical powers generated by it is about 10-13 times of magnitude greater than when illuminated with a continuous wave of equivalent average power, which can be effectively used for particle trapping and nanomanipulation [36,37], particularly for use in microscopes.…”
Section: Discussionmentioning
confidence: 99%